Use of Faceted Search: The Effect on Researchers - Mahdi M.N.; Ahmad A.R.; Qassim Q.S.; Subhi M.A. (Springer Science and Business Media Deutschland GmbH, 2023)
Information retrieval; Semantics; Websites; Energy; Exploratory search; Faceted energy; Faceted search; Information overloads; Performance; Research topics; Search operations; Search technique; Web searches; Search engines